DEVELOPMENT OF ULTRASONOGRAPHY FOR DOWNHOLE WELL INSPECTION - Gathuk Widiyanto (Scientific Contributions Oil and Gas, 2014)
One technique to increase oil production rate in marginal and suspended wells is solving mechanicalproblem. Success parameter to solve the mechanical problem is to identify this problem properly andaccurately. One of the tools to identify the well integrity including mechanical problem in oil and gasindustry is downhole camera used to describe bore hole conditions. Image is very important and is usedas main parameter to determine the production and operation strategy. So, imaging technology transfer isvery important especially on proven technology. Ultrasonography is proven technology in medical disciplineto create image within human body without signifi cant error. This research tries to apply ultrasonographytechnology in oil and gas industry. Recently, design and prototype of downhole inspection tools stage III havebeen completed. Prototype consists of electronic system, mechanical system and information system includedacquisition system. Laboratory test of these tools has been conducted successfully. Acquisition system usesmemory system within dry battery to avoid operation problem at fi eld test. Several advantages of this toolsare the small number data as per user’s required, user friendly and simple in operation.